Questions of the Republic of Kazakhstan social and labor legislation (Journal of actual problems of jurisprudence, 2018)
Now the human right on social security is legal expression of social policy which can be defined as use of the political power for development of economic system to achieve results which the economic system can’t reach in itself. Social policy is used for realization of social justice, social equality which excludes elementary social inequality. Social policy has to guarantee to the person worthy life. Conditions of worthy life and free development also his families are recorded in the right to the sufficient standard of living for him. Sufficient nutrition, clothes and the dwelling have to be provided to any person, conditions of his life have to improve continuously. In the modern legal doctrine social function of the state have found reflection in the constitutional fixing of the status of the social state (the Constitution of Germany, France, Spain, Italy, Portugal, the Netherlands, the Russian Federation, Kazakhstan, Armenia, Republic of Belarus). The social state is the characteristic (principle) relating to constitutional legal status of the state, assuming the constitutional guaranteeing the economic and social rights and freedoms of the person and citizen and the corresponding obligations of the state. This characteristic means that the state serves society and seeks to exclude or minimize unjustified social distinctions (Suhareva A.Ja., 1997: 647).Main objective of the research is studying of questions of social and labor status of the population,ways of improvement of the national legislation.Key words: labor, social legislation, social security, unemployment.